Management and organisational behaviour - Bloisi, Wendy; Cook, Curtis W.; Hunsaker, Phillip L. (McGraw Hill Education, 2007)
This text integrates management and organizational behaviour. Through contemporary discussion of key concepts, it aims to offer students applied behavioural skills and an understanding of how organizations function.